THEORETICAL AND METHODOLOGICAL ASPECTS OF PREPARING FOR SCIENTIFIC RESEARCH ACTIVITIES (SCIENCE TIME JOURNAL, 2026)
In the modern world, advancing science, overcoming challenges in education and research requires reforming higher education. This article discusses the requirements for the content and structure of students’ research activities in the field of pedagogy. It highlights the importance of a scientific-theoretical approach to the educational process when guiding students in their research work.